Evaluating speech recognition threshold (SRTn) of the Malay digit triplet test (MDTT) in domestic usage - Jamaluddin, Saiful Adli; O'beirne, Greg A.; Mohd Zamri, Nursyaza Liyana (Kulliyyah of Allied Health Sciences, IIUM, 2018)
Online self-screening test using speech audiometry in noise offers a new approach to screen for hearing disability from homes and facilitate in creating hearing awareness to the general public. Therefore, the purpose of this study is to evaluate the speech recognition threshold (SRTn) of the Malay Digit Triplet Test (MDTT) in domestic usage.